First report of grapevine Pinot gris virus infecting grapevine in Argentina - Debat, Humberto Julio; Luna,Facundo; Moyano, Sabrina Noé; Zavallo, Diego; Asurmendi, Sebastian; Gomez Talquenca, Gonzalo (Springer, 2020)
Fourteen viruses have been associated to grapevine in Argentina (Debat et al. 2020; Luna et al. 2019). Grapevine Pinot gris virus (family Betaflexiviridae; genus Trichovirus, GPGV) was originally described in Italy and linked to grapevine leaf mottling and deformation (GLMD) in Vitis vinifera cv. Pinot gris (Giampetruzzi et al. 2012). In Latin America, GPGV has been detected in Brazil, Chile and Uruguay.